Metamaterials for Improving Efficiency of Magnetic Resonant Wireless Power Transfer Applications - Pham, Thanh Son; Nguyen, Thao Duy; Vu, Dinh Lam (Communications in Physics, 2022)
In this article, we investigate a compact metamaterial structure for enhancing a magnetic resonant wireless power transfer (WPT) system operated at 6.5 MHz. A thin magnetic metamaterial (MM) slab placed between the transmitter (Tx) and receiver (Rx) coil can improve WPT efficiency. The metamaterial unit cell is designed by a ten-turn spiral resonator (10T-SR) loaded with an external capacitor. The resonant frequency of MM unit cells can be easily controlled by changing the capacitor value. By using the optimization approach, we achieve a significant WPT efficiency improvement at a mid-range distance. The results showed an enhancement of the magnetic field in the WPT system when MM slab was present. This demonstrates the ability to amplify the evanescent wave of MM slab, thereby improving the WPT efficiency. The transmission coefficients of WPT system at 60 cm increased from 0.5 to 0.76 with MM slab, which corresponds to a 46% improvement.